Cystathionine gamma lyase aggravates orthodontic root resorption in mice - Lu, Caizhu (Ann Transl Med, 2019)
BACKGROUND: This study aimed to determine the contribution of cystathionine gamma lyase (CSE) to physiological and orthodontic root resorption in mice. METHODS: Mice genetically deficient in the CSE (CSE(-/-)), the dominant hydrogen sulfide (H(2)S)—generating enzyme in osteoclast were used in this study. Physiological and orthodontic root resorption was assessed with micro computed tomography (micro-CT) and scanning electron microscopy (SEM) in the mice at the age of 8-, 26-, and 52-week and in 8-week old mice following 1-, 2-, and 3-week orthodontic treatment, respectively. Hematoxylin and eosin (HE) and tartrate-resistant acid phosphatase (TRAP) staining were used for further determination of root resorption and the number of osteoclasts. The receptor activator of nuclear factor kappa-B ligand (RANKL)/osteoprotegerin (OPG) level in surrounding alveolar bone of the maxillary first molar after 2-week orthodontic treatment was measured by reverse transcription polymerase chain reaction (RT-PCR). RESULTS: Root resorption lacunae (RRL) gradually and significantly increased with age in wild type (WT) and CSE(-/-) mice. The CSE(-/-) showed less RRL compared with the WT group. At each time point of orthodontic treatment, the CSE(-/-) group had less RRL and osteoclasts than the WT group. The orthodontically induced RANKL/OPG mRNA expression in the periodontal tissue in the CSE(-/-) group was lower than that in the WT group. CONCLUSIONS: CSE contributes significantly to physiological and orthodontic root resorption.